Differences in Clinical Measures and Outcomes in South Asians vs Caucasians Attending Cardiac Rehabilitation - Gami L. Nanayakkara, BSc; Tracey Rai, RDN; Lena Kirincic, RN; Rhonda Lightfoot, RN; Janek M. Senaratne, MD, MSc, FRCPC, FACC; Manohara Senaratne, MD, PhD, FACC (CJC Open, 2021)
Background: South Asians have a greater predisposition to cardiac events, compared to Caucasians. Although cardiac rehabilitation programs (CRPs) are known to improve outcomes, data are sparse regarding benefits acquired by South Asians vs Caucasians. The objective of the current study was to determine the outcomes of South Asian patients undergoing CRPs, compared to Caucasian patients. Methods: This study compared baseline characteristics and outcomes in all patients attending a CRP in Edmonton, Canada with a proportionately large South Asian population. Results: From 1998 to 2016, a total of 811 South Asians and 5406 Caucasians attended CRPs. Baseline characteristics revealed that there were more nonsmokers (73.4% vs 29.4%, P < 0.001), with a lower body mass index (26.8 ± 0.1 vs 29.6 ± 0.1, P < 0.001), but higher prevalence of diabetes (37.7% vs 20.5%, P < 0.001) in the South Asian population. Outcome measures revealed that South Asians spent less time in the CRP (6.9 weeks ± 0.1 vs 7.3 weeks ± 0.1, P < 0.001), attended the nutrition class less (36.2% vs 53.4%, P < 0.001), and had a lower 6-minute walk improvement (66.9 m vs 73.6 m, P < 0.001). Frequency of use of β-blockers (86.9% vs 86.1%, P > 0.05), antiplatelet agents (96.3% vs 97.1%, P > 0.05), angiotensin-converting enzyme inhibitors (79.9% vs 80.0%, P > 0.05), and cholesterol-lowering agents (91.4% vs 93.8%, P > 0.05) was not significantly different. Conclusions: Although South Asians seem to be prescribed and use proven pharmacologic treatments to the same extent as Caucasians, they appeared to benefit less from CRPs. Given higher event rates in South Asians, consideration should be given to altering the delivery of CRPs to South Asians to improve their efficacy. Résumé: Contexte: Les Asiatiques du Sud sont davantage prédisposés aux événements cardiaques que les Caucasiens. Si l'on sait que les programmes de réadaptation cardiaque (PRC) permettent d'améliorer les résultats, rares sont cependant les données sur les effets bénéfiques des PRC chez les Asiatiques du Sud comparativement aux Caucasiens. L'objectif de la présente étude était de comparer les résultats obtenus par les patients sud-asiatiques ayant suivi un PRC à ceux des patients caucasiens. Méthodologie: Dans cette étude, nous avons comparé les caractéristiques initiales et les résultats de tous les patients ayant suivi un PRC à Edmonton, au Canada, qui compte une population sud-asiatique proportionnellement importante. Résultats: Entre 1998 et 2016, 811 patients sud-asiatiques et 5406 patients caucasiens ont suivi des PRC. L'examen des caractéristiques initiales montre que les patients sud-asiatiques étaient plus souvent des non-fumeurs (73,4 % vs 29,4 %, p < 0,001) et présentaient un indice de masse corporelle inférieur (26,8 ± 0,1 vs 29,6 ± 0,1, p < 0,001), mais une prévalence du diabète plus élevée (37,7 % vs 20,5 %, p < 0,001) que les patients caucasiens. Les mesures des résultats ont révélé que les patients sud-asiatiques avaient consacré moins de temps au PRC (6,9 semaines ± 0,1 vs 7,3 semaines ± 0,1, p < 0,001), avaient moins assisté au cours sur la nutrition (36,2 % vs 53,4 %, p < 0,001), et avaient obtenu une amélioration plus faible de leur résultat au test de marche de 6 minutes (66,9 m vs 73,6 m, p < 0,001). Aucune différence significative entre les deux groupes n'a été observée en ce qui concerne la fréquence d'utilisation des bêtabloquants (86,9 % vs 86,1 %, p > 0,05), des agents antiplaquettaires (96,3 % vs 97,1 %, p > 0,05), des inhibiteurs de l'enzyme de conversion de l'angiotensine (79,9 % vs 80,0 %, p > 0,05) et des hypocholestérolémiants (91,4 % vs 93,8 %, p > 0,05). Conclusions: Si les Asiatiques du Sud se voient prescrire et utiliser des traitements pharmacologiques éprouvés dans la même mesure que les Caucasiens, ils semblent cependant retirer moins d'effets bénéfiques des PRC que ces derniers. Compte tenu de la fréquence plus élevée des événements cardiaques dans la population sud-asiatique, il y aurait lieu d'envisager la possibilité de modifier les modalités d'administration de ces programmes pour les personnes de ce groupe afin d'améliorer leur efficacité.